Serological markers for hepatitis a among captive and free-living wild mammals in the State of Pará, Brazil - Bernal, Marcella Katheryne Marques; Souza, Alex Júnior Souza de; Nunes, Heloisa Marceliano; Malheiros, Andreza Pinheiro; Chagas, André Antônio Corrêa das; Andrade, Sara Letícia dos Santos; Figueiredo, Andréa Lima Silva; Cecim, Amanda Desirée Assunção; Pereira, Washington Luiz Assunção (Semina: Ciências Agrárias, 2021)
The hepatitis A virus (HAV, Hepatovirus A) in humans has a relevant impact on public health, especially in geographic regions with poor basic sanitation, such as the Brazilian Amazon. Isolates related to hepatoviruses have been described in non human primates, chiropterans, marsupials, rodents, marmots, shrews, and terrestrial hedgehogs. However, the circulation of these viruses in the Amazonian mammal fauna remains unexplored. This study aimed to evaluate the prevalence of antibodies against this hepatovirus in captive and free-living wild mammals belonging to the orders Didelphimorphia, Primates, Carnivora, and Artiodactyla. Serum samples from 71 animals, from three municipalities in the State of Pará (Belém, Santarém, and Capitão-Poço) were tested for total anti-HAV and anti-HAV IgM through enzyme-linked immunosorbent assay (ELISA). Total anti-HAV antibodies were detected in 29.5% (21/71) of non-human primates, 8.4% (6/71) of carnivores, and 5.6% (4/71) of didelphos. All tayassuidos 0% (0/2) were seronegative. Anti-HAV IgM antibodies were not detected in any of the samples tested. The highest total anti-HAV seropositivity in the municipalities studied was in Santarém with 54.24% (12/22), followed by Capitão Poço with 50% (15/30), and then Belém with 21.05% (4/19). Among the seropositive animals, animals kept in exposure cages showed 43.9% (18/41), quarantined animals with 60% (9/15), and free-living animals with 26.6% (4/15). The serological results indicated a profile of previous exposure to hepatovirus among these animals. Therefore, additional studies to characterize HAV-related viruses in captive and free living wild animals need to be conducted to better understand the impact of the circulation of this virus on human and animal health.